Sequencing patterns of ventilatory indices in less trained adults - Pühringer, Martin; Ring-Dimitriou, Susanne; Iglseder, Bernhard; Frey, Vanessa; Trinka, Eugen; Paulweber, Bernhard (Frontiers in Sports and Active Living, 2023)
Submaximal ventilatory indices, i.e., point of optimal ventilatory efficiency (POE) and anaerobic threshold (AT), are valuable indicators to assess the metabolic and ventilatory response during cardiopulmonary exercise testing (CPET). The order in which the ventilatory indices occur (ventilatory indices sequencing pattern, VISP), may yield additional information for the interpretation of CPET results and for exercise intensity prescription. Therefore, we determined whether different VISP groups concerning POE and AT exist. Additionally, we analysed fat metabolism via the exercise intensity eliciting the highest fat oxidation rate (Fatmax) as a possible explanation for differences between VISP groups. 761 less trained adults (41–68 years) completed an incremental exercise test on a cycle ergometer until volitional exhaustion. The ventilatory indices were determined using automatic and visual detection methods, and Fatmax was determined using indirect calorimetry. Our study identified two VISP groups with a lower work rate at POE compared to AT in VISPPOE < AT but not in group VISPPOE = AT. Therefore, training prescription based on POE rather than AT would result in different exercise intensity recommendations in 66% of the study participants and consequently in unintended physiological adaptions. VISPPOE < AT participants were not different to VISPPOE = AT participants concerning VO2peak and Fatmax. However, participants exhibiting a difference in work rate (VISPPOE < AT) were characterized by a higher aerobic capacity at submaximal work rate compared to VISPPOE = AT. Thus, analysing VISP may help to gain new insights into the complex ventilatory and metabolic response to exercise. But a methodological framework still must be established.